Land Readjustment in Challenging Contexts: A Case Study of Informal Settlements in Kabul, Afghanistan - Mohammadi, Hossein (Curtin University, 2019)
Using the case of Kabul, the thesis examines land readjustment in challenging contexts with complicated land ownership, non-existent legal support, weak government capacity and unstable security conditions. By developing the theory and concept of Customised Land Readjustment, the research highlights how sustainable development can be facilitated through better management, financial, legal and technical strategies which ensure land tenure security and provision of required infrastructure. This supports improved quality of life while maintaining communities’ spatial integrity.